Integrative Effects of Vine Water Relations and Grape Ripeness Level of Vitis vinifera L. cv. Shiraz/Richter 99. II. Grape Composition and Wine Quality - Hunter, J.J.; Volschenk, C.G.; Novello, V.; Pisciotta, A.; Booyse, M.; Fouché, G.W. (South African Journal of Enology and Viticulture, 2016)
Regulation of grapevine water status is a common practice to manipulate grape composition and wine quality. In this investigation the effect of plant water status (two field water capacity-based irrigation levels, 75% and 100%, applied at single and combined vine developmental stages) and ripeness level (harvesting at different soluble solid levels) on grape composition and wine quality of Vitis vinifera L. cv. Shiraz/ Richter 99 was determined. Integrative effects of vine water relations and grape ripeness level, specifically in a Mediterranean high winter rainfall area, have not yet been investigated systematically. Source:sink mechanisms and dynamics and compositional and physical changes during both green berry and ripening periods (and in response to environment changes), seemed critical for the final grape composition and wine quality/style. Despite relatively favourable conditions of the experiment terroir, additional water was still required to obtain best grape and wine quality. Skin colour and total phenolic contents were stimulated in particular by 75% (field water capacity) pea size (PS) irrigation, post-véraison (PV) irrigation and 75% pea size+post-véraison irrigation, until the last harvest stage. Treatments that included post-véraison irrigation were not negative in terms of ripening parameters. Increasing total soluble solids with ripening were not followed in parallel by anthocyanin potential. Anthocyanin extractability increased with ripening. A late, overripe harvest may result in wines that are slightly better coloured, but highly alcoholic and tannic. Furthermore, at high ripeness level, differences between treatments largely diminished. Over-ripeness of grapes may have tempering and even negative effects on expected outcomes of seasonal cultivation efforts to produce unique wines. This would not favour economic viability. Although non-irrigated wines failed to result in exceptional wine quality at any harvest stage, a better result in overall quality was obtained in comparison to irrigation treatments applied at all stages. Berry and wine composition results corresponded with findings on wine sensorial quality. The 75% PS, PV irrigation, and 75% PS+PV irrigation consistently resulted in good quality wines. At the first harvest stage, 75% PV, 100% PV, 75% PS+V and 75% PS+PV irrigations gave most prominent wines; at the second harvest stage, vines irrigated 75% at PS, 75% at PS+PV and 75% at PV delivered most prominent wines; and at the third harvest stage, 75% PV, 100% PV, 75% PS and 75% PS+PV resulted in most prominent wines. These treatments represented different wine styles at each harvest stage. Restricted PS irrigation and PV irrigation, as single or combined treatments, featured prominently in favouring grape and wine composition and wine sensorial quality. Physical and compositional changes in ripening berries and the impact on wine quality and style were further clarified. New perspectives on managing time of harvesting with varying vine water status are given. Recommendations on vine water status management strategies required to obtain different grape composition and wine style are made.